2018
DOI: 10.1039/c8cp03984d
|View full text |Cite
|
Sign up to set email alerts
|

pH switch for OH-photoacidity in 5-amino-2-naphthol and 8-amino-2-naphthol

Abstract: Photoactive charge transfer compounds are of strong interest for their potential applications in material, chemical, and biological science and their abilities to elucidate fundamental charge transfer mechanisms. Aminonaphthols, photoacids with both oxygen (OH) and nitrogen-based (NH2) protonation sites, have been reported to undergo simultaneous excited-state proton transfer (ESPT) in water upon excitation. In this paper, the ESPT mechanism for zwitterion formation in 8-amino-2-naphthol (8N2OH) and 5-amino-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…All the differences, observed in high pH region were found to be fully reversible. The pattern of pH dependence is similar to that observed for naphtol derivatives due to OH-proton acidity (pKa(OH) ~ 9.5), leading to the formation of naphtolate anion at pH>9 [24]. The reversible nature of TcmX UV absorbance changes suggests the stability of the compound under basic conditions.…”
Section: Spectral Characteristics Of Tetracenomycinssupporting
confidence: 70%
“…All the differences, observed in high pH region were found to be fully reversible. The pattern of pH dependence is similar to that observed for naphtol derivatives due to OH-proton acidity (pKa(OH) ~ 9.5), leading to the formation of naphtolate anion at pH>9 [24]. The reversible nature of TcmX UV absorbance changes suggests the stability of the compound under basic conditions.…”
Section: Spectral Characteristics Of Tetracenomycinssupporting
confidence: 70%
“…It is unclear whether the electronic effects of the functional groups will thus be equally weighted. Previous spectral studies on the photochemistry of aminonaphthol isomers differed on whether the protonated or deprotonated species (i.e., cation or neutral in Figure ) leads to zwitterion formation in the excited state. Our time-correlated single-photon counting (TCSPC) emission measurements on 5N2OH and 8N2OH confirmed that the excited cation is the precursor to the zwitterion . 7N2OH is still assumed to undergo zwitterion formation from the neutral state, i.e., undergo dual excited-state proton transfer (ESPT) at both functional sites, but there have been no dynamical studies to support this assignment.…”
Section: Introductionmentioning
confidence: 59%
“…For example, 1-hydroxypyrene exhibits increased photoacidity in water upon substitution by sulfonate versus sulfonamide EWG: p K a * of 1.3 for HPTS vs 0.7 for 8-hydroxy-hexamethylpyrene-1,3,6-trisulfonamide; mono- and disubstituted 5-cyano-2-naphthol (5CN2OH) and 5,8-dicyano-2-naphthol (DCN2OH) have boosted p K a * of −0.75 and −4.5 compared to 2OH, p K a * = 2.8, ,, such that proton donation can be extended beyond water to select organic solvents. Reversible protonation of functional groups provides additional flexibility in tuning the photoacidity, as in 6-carboxyl-2-naphthol (6COOH2OH), the protonated and deprotonated carboxyl species have p K a *­(OH) of 1.4 vs 2.5, respectively, , while in 8-amino-2-naphthol (8N2OH), the corresponding p K a * vary more greatly, p K a *­(OH) = 1.2 vs 9.5 . In contrast, there have been few studies exploring the use of electron-donating groups (EDG) to control photoacidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 N2OH has the structure close to 1N2OH. In the literature 8 N2OH is reported to exhibit neutral, cation, and Zwiter ion forms [46] in water. In case of the MWCNT-1N2OH, we have observed the red shift due to the π-π interaction of 1N2OH with MWCNT, and this could be partly due to formation of polaron in the π stack of 1N2OH on MWCNT due to the electron donor-acceptor (EDA) interaction [47][48][49] which induces the formation of localized electronic states within the bandgap of the MWCNT-1N2OH system.…”
Section: Physical Characterizations Of the Modified Electrodementioning
confidence: 99%